Word of Mouth (WoM) dalam Komunikasi Pemasaran Industri Rumah Tangga (IRT) Jamu di Pamekasan Madura - Nugraheni, Ning Izmi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Herbal medicine businesses should no longer use traditional marketing communications instead they have switched to using modern marketing communications. However, the fact is that traditional marketing communications are still widely applied by jamu entrepreuners in the field. In fact, it was able to make the herbal medicine business continue to thrive and exist tday amidst the proliferation of modern pharmaceutical drugs and herbal products from foreign countries. The WoM phenomenon of the Madura Pamekasan herbal home industry was researched using descriptive qualitative research methods to describe events that occurred in the field. The results of research on WoM in marketing communications for the herbal home industry in Pamekasan Madura are the tendency for the Pamekasan Madura herbal home industry to use Madura language, combining sales promotion through local events, WoM bay consumer through recommendations and tetimonilas, woM bay consumers through reseller and tendencies. Pamekasan Madura herbal medicine does not implement planning.